Non invasive ventilation and the high-flow nasal circuit (Research, Society and Development, 2023)
The purpose of this study is to discuss non-invasive ventilation and the High Flow Nasal Circuit (HFNC). The therapy is used by intensivists in Intensive Care Units – ICUs. It is a non-invasive breathing support modality that delivers heated and humidified gas mixtures to bedridden patients through a nasal cannula. The methodology used for the theme occurred in the online databases, Virtual Health Library (VHL) and Scientific Electronic Library Online (SCIELO). For greater reliability of the articles, a bibliographical survey of relevant studies was carried out, using keywords on the subject, and the selected articles had as criteria: clinical studies published in the last ten years. this new technique as a means of non-invasive ventilatory support, aims to provide the patient with greater comfort, improved oxygenation, reduced need for invasive mechanical ventilation and reduced reintubation rates. Because it is a new alternative, new studies must be carried out in the scientific academy.